Inferring behavioural mechanisms in habitat selection studies getting the null‐hypothesis right for functional and familiarity responses. Issue 3 (21st September 2012) - Van Moorter, Bram; Visscher, Darcy; Herfindal, Ivar; Basille, Mathieu; Mysterud, Atle
<x xml:space="preserve">Abstract</x> Recent studies of animal habitat selection are inferring more detail regarding the behavioural mechanisms involved, like functional responses and familiarity effects. Changes in animals' use or selection of a habitat type with changing availability are commonly interpreted as a functional response in habitat preference. Studies of familiarity inferred preference for familiar locations from selection for previously visited locations after accounting for habitat‐related preference. We simulated movement paths on discrete landscapes using random walk models with known habitat selection behaviour to assess emergent properties related to habitat selection in the context of functional and familiarity responses. The behavioural interpretation of functional responses relies on the relationship between habitat use and preference. Unfortunately, this relationship is not unique and depends upon the habitat choice mechanism: habitat use can be proportional to preference or proportional to availability (called respectively, hierarchical and simultaneous choice). We found that when the analytical method did not match the choice mechanism, strong functional responses were observed in habitat selection, even though habitat preference was kept constant. Therefore, functional responses need to be discussed in the context of an animal's habitat choice mechanism. In the absence of familiarity‐related preference, we found no familiarity effect while accounting for all habitat variables. However, when habitat models were incomplete (e.g. lack of information about resources and habitats in the landscape) – as in all field studies – spurious preference for familiar locations arose. Our study aids the interpretation of behavioural mechanisms in habitat selection studies, but also calls for a more thorough study of the approaches used to infer behavioural mechanisms in habitat selection studies.